Penggunaan Media Kartu Emosi Bergambar Untuk Memahami Jenis-Jenis Emosional Anak Usia Dini - Yodelara Yodelara; Dwi Nomi Pura; Rika partikasari (Early Childhood Research and Practice, 2026)
The ability to understand emotions is a crucial aspect of early childhood socio-emotional development that requires appropriate stimulation during the "golden age" period. Preliminary observations at PAUD Aulia Tusyifa (Lubuk Sini Village, Taba Penanjung District, Central Bengkulu Regency) revealed that most children in Group B (aged 5–6 years) struggled to recognize and distinguish between various emotions—particularly complex ones such as shame, confusion, annoyance, disgust, mockery, and fatigue. Furthermore, the teaching methods employed were conventional and lacked support from concrete visual aids. This study aimed to describe the use of illustrated emotion cards in instruction, assess children's understanding of different emotions after using these cards, and identify the supporting and inhibiting factors involved. A descriptive study with a qualitative approach was conducted, involving a school principal, three Group B teachers, and five boys (aged 5–6 years) as research subjects. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles, Huberman, and Saldaña model. The results demonstrated that the systematic use of illustrated emotion cards—incorporating card recognition, question-and-answer sessions, storytelling, and reflection—was effective in helping children recognize the eleven introduced emotions, verbally express their feelings, and foster empathy toward their peers. Four of the five children met all performance indicators, while one child had not yet achieved the indicator for speaking confidently in front of the class. These findings highlight the need for the sustained use of concrete visual learning aids within the early childhood education curriculum to optimize children's socio-emotional development.